tính:
\(4\frac{5}{6}+\frac{1}{6}.\left(8-2\frac{2}{3}\right)\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(=\dfrac{35.85\cdot14}{0.5+2.3}\cdot\dfrac{6}{17}\cdot\dfrac{16.8}{259,2}-\left(4.625-\dfrac{13}{6}:\dfrac{26}{3}\right):\left(3.25:2.25\right)\)
\(=\dfrac{1673}{408}-\dfrac{315}{104}=\dfrac{1421}{1326}\)
\(\begin{array}{l}a)\left( {\frac{2}{3} + \frac{1}{6}} \right):\frac{5}{4} + \left( {\frac{1}{4} + \frac{3}{8}} \right):\frac{5}{2}\\ = \left( {\frac{4}{6} + \frac{1}{6}} \right).\frac{4}{5} + \left( {\frac{2}{8} + \frac{3}{8}} \right).\frac{2}{5}\\ = \frac{5}{6}.\frac{4}{5} + \frac{5}{8}.\frac{2}{5}\\ = \frac{2}{3} + \frac{1}{4}\\ = \frac{8}{{12}} + \frac{3}{{12}}\\ = \frac{{11}}{{12}}\\b)\frac{5}{9}:\left( {\frac{1}{{11}} - \frac{5}{{22}}} \right) + \frac{7}{4}.\left( {\frac{1}{{14}} - \frac{2}{7}} \right)\\ = \frac{5}{9}:\left( {\frac{2}{{22}} - \frac{5}{{22}}} \right) + \frac{7}{4}.\left( {\frac{1}{{14}} - \frac{4}{{14}}} \right)\\ = \frac{5}{9}:\frac{{ - 3}}{{22}} + \frac{7}{4}.\frac{{ - 3}}{{14}}\\ = \frac{5}{9}.\frac{{ - 22}}{3} + \frac{{ - 3}}{8}\\ = \frac{{ - 110}}{{27}} + \frac{{ - 3}}{8}\\ = \frac{{ - 880}}{{216}} + \frac{{ - 81}}{{216}}\\ = \frac{{ - 961}}{{216}}\end{array}\)
a, \(\frac{\left(\frac{1}{9}\right)^6\cdot\left(\frac{3}{8}\right)^7}{\left(\frac{1}{3}\right)^{13}\cdot\left(\frac{1}{2}\right)^{22}.3^6}\)
\(=\frac{\left(\frac{1}{\left(3^2\right)^6}\right)\cdot\left(\frac{1}{2}\cdot\frac{1}{2}\cdot\frac{1}{2}\cdot3\right)^7}{\left(\frac{1}{3}\right)^{13}.\left(\frac{1}{2}\right)^{22}.3^6}=\frac{\frac{1}{3^{12}}\cdot\left(\frac{1}{2}\right)^{21}\cdot3^7}{\frac{1}{3^{13}}\cdot\left(\frac{1}{2}\right)^{22}.3^6}\)
\(=\frac{3}{\frac{1}{3}\cdot\frac{1}{2}}=3\div\frac{1}{6}=3.6=18\)
b, Làm tương tự nha bn
\(4\frac{5}{6}+\frac{1}{6}.\left(8-2\frac{2}{3}\right)\)
\(=\frac{29}{6}+\frac{1}{6}.\left(8-\frac{8}{3}\right)\)
\(=\frac{29}{6}+\frac{1}{6}.\left(\frac{24}{3}-\frac{8}{3}\right)\)
\(=\frac{29}{6}+\frac{1}{6}.\frac{16}{3}\)
\(=\frac{29}{6}+\frac{8}{9}\)
=\(=\frac{103}{18}\)
\(4\frac{5}{6}+\frac{1}{6}.\left(8-2\frac{2}{3}\right)\)
\(=\frac{29}{6}+\frac{1}{6}.\left(8-\frac{8}{3}\right)\)
\(=\frac{29}{6}+\frac{1}{6}.\left(\frac{24}{3}-\frac{8}{3}\right)\)
\(=\frac{29}{6}+\frac{1}{6}.\frac{16}{3}\)
\(=\frac{29}{6}+\frac{8}{9}\)
\(=\frac{87}{18}+\frac{16}{18}\)
\(=\frac{103}{18}\)